Potentialities and vulnerabilities of the hypertension program: a review study (Research, Society and Development, 2020)
The health actions employed in the program comprise annual or quarterly medical consultations, according to the protocol, which include clarifications and guidelines consistent with arterial hypertension, guidelines and blood pressure measures by the nursing team, meetings and lectures held by unit and medication dispensation, but we still found low adherence to treatment, therefore, this study aimed to assess the reasons that lead to low adherence, by means of a bibliographic study on the scientific works published by undergraduate students from the University of the State of Pará, where they were found as main problems of services, infrastructure, high demand in health services, information related to the importance of home care about this disease, among others, which leads us to conclude that there must be continuous improvement of the health team, based on agents, technicians and higher education professionals, so that by having contact with these If these individuals are infected by a chronic process, it is possible to accept and meet the demand to increase adherence.